Disability and sport as a tool to redefine social identity. The Content Analysis of some statements by disabled people - Simonetta Secondini (Technium Social Sciences Journal, 2020)
The aim of the present work is to underline that the partecipation in sport activies may be linked to identity formation and to the process of redefinition of identity, following events that led to phisical disabilities. Sport can be a tool capable of helping people with supervening disability to rebuild their identity. In addition, it may contibute to the modification of the common place which considers the disabled persons as an unfit person. In seeking to prove these assumptions, this study, by applying the Content Analysis, has qualitatively investigated, trough analyse of some open ended interviews, conducted from journalist to disabled people who practice sports, the most meanigful aspects of partecipation in adptive sports and if this partecipation can help the process of redefining of the identity or its negotiation and can help to bring out the resilient capacity of the subject.